2009
DOI: 10.3382/ps.2009-00091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different egg storage periods on some egg quality characteristics and hatchability of partridges (Alectoris graeca)

Abstract: The effect of 1 to 2-, 3 to 4-, 5 to 6-, 7 to 8-, 9 to 10-, 11 to 12-, and 13 to 14-d storage periods on quality characteristics and hatchability of partridge (Alectoris graeca) eggs was studied. There was no significant effect of storage period on egg weight, shell weight, shell ratio, and shell thickness as external quality characteristics of partridge eggs (P > 0.05). Storage periods affected internal quality characteristics of partridge eggs (P < 0.05). An increase in yolk ratio (P < 0.05) and decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 9 publications
4
7
0
Order By: Relevance
“…Stocking density has been shown to influence egg production and performance of broiler breeder hens as higher density produced fewer eggs (Mtileni et al, 2007). In addition, egg storage periods may affect fertility and hatchability in poultry chicken species (Babiker & Musharaf, 2008;Caglayan et al, 2009), and feed restrictions (Sarica et al, 2009) season, flock age and disease-vaccination conditions (Turkyilmaz et al, 2010;Holt et al, 2011) were also found to interact growing and laying performance in chickens. Recent studies have demonstrated that although maternal dietary protein level had no effect on hatchability and growth rate (Kingori et al, 2010), but age (Bekele et al, 2010) and phenotype (Haunshi et al, 2011) affected production performances of laying hens.…”
Section: Resultsmentioning
confidence: 99%
“…Stocking density has been shown to influence egg production and performance of broiler breeder hens as higher density produced fewer eggs (Mtileni et al, 2007). In addition, egg storage periods may affect fertility and hatchability in poultry chicken species (Babiker & Musharaf, 2008;Caglayan et al, 2009), and feed restrictions (Sarica et al, 2009) season, flock age and disease-vaccination conditions (Turkyilmaz et al, 2010;Holt et al, 2011) were also found to interact growing and laying performance in chickens. Recent studies have demonstrated that although maternal dietary protein level had no effect on hatchability and growth rate (Kingori et al, 2010), but age (Bekele et al, 2010) and phenotype (Haunshi et al, 2011) affected production performances of laying hens.…”
Section: Resultsmentioning
confidence: 99%
“…Eggs after 1-2 days of storage were characterized by higher values of the white and yolk indices and number of Haugh units than eggs examined in 9th or 10th day of storage. On the other hand, in the investigations carried out on the rock partridge (Alectoris graeca), no significant differences were recorded in the white index and the number of Haugh units when egg quality was analysed after 1-2 and 9-10 days of storage (CAĞLAYAN et al 2009). ŞEKEROĞLU and ALTUNTAŞ (2009), when evaluating eggs (small, medium, large and extralarge) of brown-egg layer hens, reported that yolk and albumen height increased with egg size.…”
Section: Introductionmentioning
confidence: 92%
“…The authors observed that eggs stored for 1 to 2 days had higher values in white and yolk indices and Haugh units than those examined on the 9 to 10th day of storage. On the contrary, in rock partridge (Alectorus graeca), Cağlayan et al (2009) found no significant differences in white indices and Haugh units between eggs analyzed in 1 to 2 days and 9 to 10 days of storage. In Japanese quails, Nowaczewski et al (2010) reported that eggs stored 10 days recorded lower values in yolk and albumen indices than freshly laid eggs.…”
Section: Introductionmentioning
confidence: 64%